Analisis Alur Proses Penerimaan Pasien Rawat Inap di Rumah Sakit “X” Tahun 2015 dengan Pendekatan Lean Hospital - Dewi, Pretty Kristianti (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
Lean hospital is lean methods used in hospitals, is a continuous effort made to eliminate waste and increase value added in patient care in hospitals. This method is very appropriate to analyze the process flow of inpatient admission in "X" hospital by making Current State Value Stream Map derived from observation, interviews and review of documents. Then through the application of Lean Tools, Future State Value Stream Map was made as the idea of improvement for short and medium/long term in the process. The results showed there were 31 total events with value added time process is just 44,9% at this point. Meanwhile in the new or ideal process flow, the amount of activities became 25 with value added time process 92,4% for short term improvement. The number activities on the medium/long term improvement reduced to 23 with the percentage of value added time process increased to 94,4%. So based on these results, the Lean method is appropriate to address the problems that occur in the workflow process inpatient admission in "X" hospital.